2017
DOI: 10.1021/acs.est.7b00604
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Disposition of Select Pharmaceuticals by Bluegill Exposed at Constant Concentrations in a Flow-Through Aquatic Exposure System

Abstract: The increasing use of pharmaceuticals has led to their subsequent input into and release from wastewater treatment plants, with corresponding discharge into surface waters that may subsequently exert adverse effects upon aquatic organisms. Although the distribution of pharmaceuticals in surface water has been extensively studied, the details of uptake, internal distribution, and kinetic processing of pharmaceuticals in exposed fish have received less attention. For this research, we investigated the uptake, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Similarly, malformations in zebrafish embryos were linked to maternal PFOS transfer to embryological development (Du et al ). Little is known about maternal transfer of pharmaceuticals but several studies have reported bioaccumulation of these CECs in exposed organisms (Schultz et al ; Clairardin et al ; Zhao et al ()), suggesting that maternal transfer to eggs is plausible and has been observed for other pollutants (Marsh‐Matthews et al ).…”
Section: Challenge 3: Duration Of Cec Exposure Within and Across Gene...mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, malformations in zebrafish embryos were linked to maternal PFOS transfer to embryological development (Du et al ). Little is known about maternal transfer of pharmaceuticals but several studies have reported bioaccumulation of these CECs in exposed organisms (Schultz et al ; Clairardin et al ; Zhao et al ()), suggesting that maternal transfer to eggs is plausible and has been observed for other pollutants (Marsh‐Matthews et al ).…”
Section: Challenge 3: Duration Of Cec Exposure Within and Across Gene...mentioning
confidence: 99%
“…However, PFOS has been known to bioaccumulate in aquatic organisms (Du et al 2009;Haddad et al 2017) and may lead to adverse outcome for first filial generation offspring of exposed parental organisms (Du et al 2009). Similarly, some pharmaceuticals have been reported to bioaccumulate in tissues with little knowledge of the long-term consequences (Zhao et al (2017)). Given the chemical diversity of pharmaceuticals, it is not surprising that bioaccumulation varies for these CECs.…”
Section: Challenge 3: Duration Of Cec Exposure Within and Across Gene...mentioning
confidence: 99%
See 1 more Smart Citation
“…27,56,57 Sulfamethoxazole was intermittently detected in the tissues with low concentrations in TG-10 (7.1−57.2 μg•kg −1 ), which are close to those in TG-1 (13.2−41.5 μg•kg −1 ), indicating limited uptake of sulfamethoxazole by the juveniles. Zhao et al 58 also observed restricted uptake of sulfamethoxazole in bluegill sunfish (Lepomis macrochirus) exposed to environmentally relevant concentrations. The phenomenon can be due to the predominant presence of the compound as an anionic Environmental Science & Technology pubs.acs.org/est Article species (>99%, pK a = 5.7) 59 in the seawater (pH = 8.1 in the current study) because ionic species were reported to have a slower rate to cross membranes than the corresponding neutral molecule.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…This could also affect the livelihoods of people dedicated to selling fish such as catfish, since endocrine disruption could affect the reproductive capacity of fish (Shioda and Wakabayashi, 2000), and therefore decrease fish production. The risk to the health of the human population posed by compounds of this nature, such as carbamazepine (CMZ), is aggravated by its bioaccumulation in aquatic and terrestrial organisms (Vernouillet et al, 2010), which has been reported mainly in fish (Daughton and Brooks, 2011;Du, et al, 2014;Zhao, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%